2022
DOI: 10.3390/ph15080944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Myrrh Metabolites in Cancer, Inflammation, and Wound Healing: Prospects for a Multi-Targeted Drug Therapy

Abstract: Background: Myrrh extract is a well-known medicinal plant with significant therapeutic benefits attributed to the activity of its diverse metabolites. It has promising activity against cancer and inflammatory diseases, and could serve as a potential therapeutic alternative since most therapeutic agents have severe side effects that impair quality of life. Method: The current study identified the active metabolites from the myrrh resin methanolic extract. Then, the extracts were tested for in vitro anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Other studies have also shown medicinal plants to bind to the CA IX enzyme and regulate ROS production in macrophages. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown medicinal plants to bind to the CA IX enzyme and regulate ROS production in macrophages. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown medicinal plants to bind to the CA IX enzyme and regulate ROS production in macrophages. 8,9 4-hydroxyphenyl acetic acid (4-HPA) is a polyphenol having antioxidant action and was shown to protect against paracetamol-induced liver damage by enhancing the activity of antioxidant enzymes and increasing Phase II metabolism. As such, it could be used as a naturally occurring plant-based hepatoprotective agent.…”
Section: Arboreus Metabolitesmentioning
confidence: 99%
“…Ajiteru et al 75 constructed a fabrication of myrrh resin hydrocolloid dressing called the Mirderm and reported superior wound healing and mechanical capability compared with commercial hydrocolloid and gauzes. Suliman et al 76 analyzed myrrh resin methanolic extract and found anti-inflammatory, anticancer, and wound healing effects, promoting complete re-epithelialization of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Myrrh consists of watersoluble gum, alcohol-soluble resins, and volatile oil. [13][14][15][16][17][18][19] Among them, sesquiterpenoids and triterpenoids were considered to be the main bioactive components of this herb. [20][21][22][23][24][25] Our study can provide a powerful guidance for understanding the toxic substance in Myrrh through investigation of the chemical mechanism of toxicity reduction by vinegar-processing.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, the exact mechanism and the relationship between vinegar‐processing and changes in the chemical composition of Myrrh has been poorly defined. Studies have reported that Myrrh consists of water‐soluble gum, alcohol‐soluble resins, and volatile oil [13–19] . Among them, sesquiterpenoids and triterpenoids were considered to be the main bioactive components of this herb [20–25] .…”
Section: Introductionmentioning
confidence: 99%